Unemployment and vacancies with sectoral shifts - Hosios, Arthur J. (American Economic Review, 1994)
Recent analyses of unemployment-vacancy series suggest that aggregate shocks, rather than sectoral shocks, are the primary factors responsible for unemployment fluctuations. This inference follows from two widely held beliefs: sectoral shocks induce only positive unemployment-vacancy comovements, while negative comovements are necessarily the result of aggregate demand shocks. This paper describes an equilibrium matching model that identifies plausible circumstances in which neither assumption is correct, thus suggesting that unemployment-vacancy data are inconclusive. Interestingly, this model's novel results are due to standard features in the contracting literature: firms experience relative price shocks and negotiate contracts that prescribe temporary layoffs. Copyright 1994 by American Economic Association.